2006
DOI: 10.1021/ic061081o
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Pronounced Medium Effects Observed in the Voltammetry of the Highly Charged Lacunary Anions [α-SiW11O39]8-and [α-PW11O39]7-

Abstract: A detailed study is reported of the influence of protons, metal cations, and media on the redox chemistry of lacunary anions [alpha-SiW11O39]8- and [alpha-PW11O39]7- of high formal negative charge. Each anion displayed a single chemically reversible one-electron reduction process in carefully dried aprotic CH3CN solution. This process was detected at very negative potentials just prior to the solvent limit. Addition of 0.3 equiv of acid gave rise to a new reduction process at considerably less negative potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 27 publications
3
36
0
Order By: Relevance
“…It has been reported in literature that lacunary anion with a formal charge of 7 shows one reversible redox process in aqueous buffer medium. Here too we see a single electron redox process with peat potentials at −0.7 V and −0.4 V, which is in good agreement with literature . The slight shift in the peak potentials in this case may be due to change in the counter‐cation.…”
Section: Resultssupporting
confidence: 92%
“…It has been reported in literature that lacunary anion with a formal charge of 7 shows one reversible redox process in aqueous buffer medium. Here too we see a single electron redox process with peat potentials at −0.7 V and −0.4 V, which is in good agreement with literature . The slight shift in the peak potentials in this case may be due to change in the counter‐cation.…”
Section: Resultssupporting
confidence: 92%
“…4a, b). It has been reported that the lacunary anion (PW 11 ) having a formal charge of 7 features one reversible redox process in aqueous buffered media [27]. The obtained values of Epa and Epc (-0.5 and -0.55 V, respectively,) are in good agreement with the literature, indicating one electron reduction in the lacunary anion.…”
Section: Electrochemical Studiessupporting
confidence: 88%
“…This could be due to a very thin film of the polymer remaining on top of parts of the exposed graphite particles, which reduces the ease of reduction or oxidation [31]. The mechanism will involve successive additions of electrons and protons (for reduction), as has been observed in non-aqueous solution and where it was also pointed out that there are pronounced medium effects on the observed voltammetry [42].…”
Section: Voltammetric Behaviour Of Pom-cpe 1 and Pom-cpementioning
confidence: 94%